Pentecostal ecclesiology : a reader - Green, Chris E. W. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2016, ISBN: 9789004303942., 2016)
This reader in Pentecostal ecclesiology, edited by Chris Green, brings together in a single volume a number of critically important previously-published essays written by leading Pentecostal and charismatic scholars addressing the theology of the church, sacraments, and ministry in the Pentecostal/charismatic traditions. Contributors include: Estrelda Alexander, Peter Althouse, Jonathan E. Alvarado, Ken Archer, Daniela Augustine, Simon Chan, Graciela Esparza, Jenny Everts, Chris E. W. Green, Walter Hollenweger, Cheryl Bridges Johns, Veli-Matti Kärkkäinen, Andy Lord, Frank Macchia, Clark Pinnock, Margaret M. Poloma, Lisa Stephenson, Wolfgang Vondey, and Amos Yong.